Ovarian fibromas with heavy deposition of hyaline globules: a diagnostic pitfall - Michal, Michal; Kacerovska, Denisa; Mukensnabl, Petr; Petersson, Fredrik; Danis, Dusan; Adamkov, Marian; Kazakov, Dmitry V (International journal of gynecological pathology, 2009)
We report 5 patients with cellular ovarian fibromas, which contained heavy depositions of hyaline globules, a remarkable and very conspicuous histologic feature of all tumors. The hyaline globules ranged in size from 1 to 25 microm. Some cells were stuffed with myriads of small hyaline globules 1 to 3 microm in size, whereas in the other cells the globules were up to 25 microm in size. The hyaline globules were stained with periodic acid-Schiff, and were mucicarmine and Alcian blue negative. These hyaline globules were present, at least in small numbers, in all 100 hematoxylin and eosin slides reviewed from all 5 cases in this series. Often the cells containing the hyaline globules showed a signet-ring appearance in the more compact cellular areas. All the tumors in our series appear to have a benign course. The patients were without signs of recurrence and without metastasis 1, 2, 3, and 6 years after the excision of the neoplasms. Follow-up in one of the patients was not available. The distinction of the ovarian fibromas with hyaline globules from the Krukenberg tumors and yolk sac tumor is discussed in the paper.
Keywords: diferenciální diagnóza; mladiství; imunohistochemie; nádor z entodermálního sinusu; Middle Aged; Hyalin; nádory vaječníků; Endodermal Sinus Tumor; Krukenbergův nádor; hyalin; Immunohistochemistry; ženské pohlaví; Krukenberg Tumor; Humans; lidé středního věku; Fibroma; Diagnosis, Differential; Female; Ovarian Neoplasms; Adolescent; fibrom; lidé